Using Whatsapp for Learning to Enhance Students’ Vocabulary Achievement - Chusnatayaini, Arina; Nafi’yah, Siti (Universitas Nusantara PGRI Kediri, 2024)
The aims of research were to know the effectiveness of using WhatsApp to enhance students’ vocabulary achievement, and the challenges faced in implementing this technology. The design of this research followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines to ensure a structured and transparent review process.The inclusion and exclusion criteria were determined in this study.Nineteen of the one hundred chosen articles met the inclusion requirements after further evaluation.The data were synthesized to provide a comprehensive overview of WhatsApp's influence on vocabulary learning. The synthesis highlighted the benefits, challenges, and implications of using WhatsApp in the context of language learning, managing distractions, ensuring material relevance, safeguarding privacy, and employing strategic teaching methods.As WhatsApp offers a platform for individual study outside of the classroom and peer-to-peer immediate feedback, it also encourages students' motivation and involvement in the learning process. The analysis of these results demonstrates that incorporating WhatsApp into the curriculum can create an engaging and dynamic learning environment. However, in order to fully utilize this technology for learning, this study also identified a number of obstacles that must be addressed, including problems with technological access, distractions, and managing study groups.It is clear that WhatsApp has great potential as an effective educational tool in improving EFL students' vocabulary learning. Educational institutions should consider formally integrating WhatsApp into their language learning curriculum and learning activities.